2018
DOI: 10.1080/01416200.2018.1484697
|View full text |Cite
|
Sign up to set email alerts
|

Training imams in the Netherlands: the failure of a post-secular endeavour

Abstract: What are the reasons behind the failure of the Islamic theology and imamtraining programmes at the Dutch universities? To address this question, we employed qualitative content analysis of semi-structured interviews (N = 38) conducted between July 2016 and January 2017. The sample consists of stakeholders such as academics teaching in the programmes, imams, Qur'an teachers, chairs of the largest Islamic organisations, and Dutch ministry and municipality officials. We analysed the establishment of the state-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the quality of Diyanet's mosque education was perceived higher since Diyanet imams are graduates of the Islamic Theology university programmes in Turkey and received pedagogical training, whereas in non-state affiliated mosques in the Netherlands, lower educated or self-taught imams are recurrently employed. Furthermore, 'the Diyanet imams are sent and paid by the Turkish government following an annual nationwide exam for Turkish theology graduates and an interview with a committee comprised of officials from the Turkish Ministry of Culture and the Ministry of Foreign Affairs' (Sözeri, Altinyelken, and Volman 2018). As such, Diyanet imams in the Netherlands are viewed as more knowledgeable and competent in pedagogical skills.…”
Section: Turkish Mosque Education In the Netherlands And Diyanetmentioning
confidence: 99%
“…Moreover, the quality of Diyanet's mosque education was perceived higher since Diyanet imams are graduates of the Islamic Theology university programmes in Turkey and received pedagogical training, whereas in non-state affiliated mosques in the Netherlands, lower educated or self-taught imams are recurrently employed. Furthermore, 'the Diyanet imams are sent and paid by the Turkish government following an annual nationwide exam for Turkish theology graduates and an interview with a committee comprised of officials from the Turkish Ministry of Culture and the Ministry of Foreign Affairs' (Sözeri, Altinyelken, and Volman 2018). As such, Diyanet imams in the Netherlands are viewed as more knowledgeable and competent in pedagogical skills.…”
Section: Turkish Mosque Education In the Netherlands And Diyanetmentioning
confidence: 99%
“…However, the official representatives of Turkish Islam in Europe-Diyanet among them-refrained from participating as partners in the educational project set up by the Dutch government. Diyanet interviewees of my study report that this unwillingness is due to reservations about the adequacy of the Dutch state curriculum and the competence of the teachers who would give the lessons [23]. The training of imams in Europe and the recruitment of candidates among Muslims living in Europe have not been Diyanet's priorities in recent years.…”
Section: Lack Of Language Skills and Knowledge Of The Local Culturementioning
confidence: 95%
“…As I addressed above, Turkish-Islamic communities do not impose any conditions regarding familiarity with the language and culture of the host country. Some scholars suggest that this problem stems from the desire of Turkish institutions to maintain their ideological structures in the host country [23,24]. It should be noted that when Islamic educational groups started to organize themselves in the Netherlands in the 1970s, this happened under the same impulse as in Turkey, where the Qur'ān schools undertook pioneering work in formal and informal RE for the Muslim community.…”
Section: Lack Of Language Skills and Knowledge Of The Local Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The education partner can also be confronted with mistrust. Sözeri et al (2018) concluded in their interviews with Diyanet administrators in the Netherlands that they not always agreed with the fact that non-Muslim lecturers are appointed at universities to teach Islam.…”
Section: Trust and Common Grounds For "Shared Ownership"mentioning
confidence: 99%